Six sigma and six sigma system in the function of quality and profits increase - Popović Branko; Miletić Ljiljana Z. (Journal of Engineering Management and Competitiveness, 2016)
Quality is the degree to which a set of permanent characteristics fulfills default, set, contracted or planned requirements for the result of the process (semi-finished product, product, documentation, services). There is a widespread belief in America that the quality is always determined by the user, not the supplier, because the quality is important not only because of the cost but because there is a completely different approach to maintaining the quality of the process. In Serbia, the applicable ISO 9000 family of standards which demonstrates the ability of suppliers, allows only stabilization of the current level of quality but not its increase that can be achieved only through better design and application of new materials and technologies. Application of Six Sigma is a different approach, which actually increases the level of quality and organization's profit; using modern computer technology it also allows the reduction of defects in the process, until the defects of 3.4 per million are realized as the results of the process. Since in Serbia, it is difficult to achieve, the authors have developed a special system of Six Sigma System, which allows realisation of a number of projects for reduction of possible costs, shortening time rational, radical elimination of losses, significante increase of the quality of the process and increase of organizations' profit.